2004
DOI: 10.2165/00023210-200418020-00003
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Induced Myoclonus

Abstract: Myoclonus is a sudden, abrupt, brief, 'shock-like' involuntary movement caused by muscular contractions ('positive myoclonus') or a sudden brief lapse of muscle contraction in active postural muscles ('negative myoclonus' or 'asterixis'). Various disorders can cause myoclonus including neurodegenerative and systemic metabolic disorders and CNS infections. In addition, myoclonus has been described as an adverse effect of some drugs. Level II evidence is available to indicate that levodopa, cyclic antidepressant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(22 citation statements)
references
References 179 publications
0
22
0
Order By: Relevance
“…Among antibiotic subgroups, beta-lactams, quinolones, sulfonamides or aminoglycosides can be found responsible most frequently. Furthermore, levodopa, dopamine agonists, anticonvulsant drugs, non-steroidal anti-inflammatory drugs, bismuth salts, lithium, amantadine, memantine, metoclopramide, calcium antagonists, corticosteroids, opioids, contrast media, chemotherapeutic drugs, propofol, as well as chronic intoxication with toluene, gasoline sniffing or substance withdrawal may be causally related [ 25 , 71 , 159 , 161 , 162 ]. With long-time antipsychotic use, a rare tardive myoclonus may occur.…”
Section: Medication and Toxin-induced Myoclonusmentioning
confidence: 99%
“…Among antibiotic subgroups, beta-lactams, quinolones, sulfonamides or aminoglycosides can be found responsible most frequently. Furthermore, levodopa, dopamine agonists, anticonvulsant drugs, non-steroidal anti-inflammatory drugs, bismuth salts, lithium, amantadine, memantine, metoclopramide, calcium antagonists, corticosteroids, opioids, contrast media, chemotherapeutic drugs, propofol, as well as chronic intoxication with toluene, gasoline sniffing or substance withdrawal may be causally related [ 25 , 71 , 159 , 161 , 162 ]. With long-time antipsychotic use, a rare tardive myoclonus may occur.…”
Section: Medication and Toxin-induced Myoclonusmentioning
confidence: 99%
“…The causes of spinal myoclonus are varied and include tumors, infection, trauma, and degenerative disease. An additional cause is adverse effects of certain drugs, administered via neuraxial routes [2]. However, spinal myoclonus following spinal anesthesia is extremely rare, and only a few cases have been reported.…”
mentioning
confidence: 99%
“…In the literature about drug-induced MCL, the most common hypothesis is associated with the serotoninergic neurotransmission. This abnormal movement was already reported with the increase and the decrease of serotonin concentration [137]. In this context, CNZ/ FNZ was first believed to decrease the serotonin concentration, in the synaptic, by the induction of monoaminergic neuron damage probably because the higher number of reports with depressive symptoms in the clinical practice [10], but some studies have shown a contradictory increase of the serotonin that happened due to serotonin reuptake blockage and facilitation of its release [7].…”
Section: Myoclonus (Mcl)mentioning
confidence: 83%